Optimal Power Flow Algorithm Based on Second-Order Cone Relaxation Method for Electricity-Gas Integrated Energy Microgrid - Fan Zhang; Zhuzheng Shen; Wen Xu; Guofeng Wang; Biyi Yi (Complexity)
Due to the existence of nonlinear constraints, it is difficult to solve the power flow directly. This paper proposes a microgrid optimal scheduling strategy using second-order cone relaxation method to realize linear transformation, so as to minimize the total cost of the microgrid. Firstly, a microgrid system model of electricity-gas integrated energy is established, and the nonlinear constraints of branch power flow are transformed by the second-order cone relaxation method. Then, based on the microgrid model, the application conditions of the second-order cone relaxation transformation method are studied, and the optimal scheduling strategy with the total cost of microgrid as the objective function is proposed. In addition, in the case that the microgrid system does not meet the application conditions of second-order cone programming, the optimization problem is solved by increasing the line loss. Finally, an example is given to verify the effectiveness of the proposed method.